The Existence of Pesantren: Implication Study of Pesantren Leadership Regeneration in Central Java - Imam Azro’i; Isyrokh Fuaidi (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
Pesantren is an Islamic educational institution with high dependency on their leader namely Kiai. The differences of competencies among their successors contributed to the decreasing of pesantren development. This research is conducted to answer the issue of sustainability in the leadership regeneration system of pesantrens in Central Java, and its implications to sustaining pesantren. Data is collected using interview, observation and documentation. The research indicated that regeneration system in pesantren have three typologies: genealogy, professional, and genealogy-professional. Pesantren salaf or traditional pesantren use genealogy, modern pesantren use professional, and semi-modern pesantren use genealogy-professional. The research had information also regarding how to sustain the pesantren and showed that the leader of pesantren salaf try to hardly keep the founding father values particularly to be adapted in the educational curriculum. Modern pesantren use a modern managerial system to sustain their institution, while semi-modern pesantren keep the development by building various educational institution.